Secondary ion mass spectrometry for Mg tracer diffusion: issues and solutions. (28th July 2014) - Tuggle, Jay; Giordani, Andrew; Kulkarni, Nagraj; Warmack, Bruce; Hunter, Jerry; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; Yi, Keewook; et al.
<x xml:space="preserve">Abstract</x> A secondary ion mass spectrometry (SIMS) method has been developed to measure stable Mg isotope tracer diffusion. This SIMS method was then used to calculate Mg self‐diffusivities, and the data was verified against historical data measured using radiotracers. The SIMS method has been validated as a reliable alternative to the radiotracer technique for the measurement of Mg self‐diffusion coefficients and can be used as a routine method for determining diffusion coefficients. Copyright © 2014 John Wiley & Sons, Ltd.